Antigen detection in primary HIV infection. Issue 6617 (23rd January 1988) - von Sydow, M; Gaines, H; Sönnerborg, A; Forsgren, M; Pehrson, P O; Strannegård, Ö
Abstract : Serial blood samples were obtained from 21 homosexuals who had developed symptomatic primary infection with human immunodeficiency virus (HIV) after a median incubation time of 14 days. During the first two weeks after the onset of illness HIV antigen (p24) was detected in the blood by enzyme linked immunosorbent assay (ELISA). During the second and third weeks after the onset of illness p24 antibody was detected by Western blot assay and antigen concentrations rapidly decreased to undetectable values. Dissociation of antigen-antibody complexes showed complexed antigen during the phase of declining concentrations of free antigen. Neither free nor complexed antigen was detected in any serum samples for several months thereafter, which suggested that failure to detect HIV antigen reflected low or absent synthesis of viral protein rather than masking of antigen by antibodies. Reappearance of HIV antigen with a fall in p24 antibody concentration was observed in a few patients six months or more after the onset of disease. The combined use of antigen and antibody assays made it possible to obtain evidence of infection with HIV in all of the 95 serum samples tested, illustrating the usefulness of these assays for diagnosing infection with HIV in its early stages.